Does increased endometrial thickness have any effect on pregnancy rates after ICSI-ET? [Artmiş endometriyum kalinliǧi ICSI-ET sikluslarinda gebelik başarisini etkiler mi?] - (:unkn) unknown (My University, 2005)
OBJECTIVES: To analyze the effect of increased endometrial thickness on pregnancy rates after ICSI-ET. STUDY DESIGN: 159 ICSI-ET cycles, which were performed between the dates of February 2002 and December 2003 in our university, were analyzed in this retrospective study. Cycles with an endometrial thickness of >6 mm on the day of hCG administration, were included into the study. The parameters for the transfer technique and embryo characteristics, and the endometrial thickness were compared between cycles, which resulted in pregnancy, and those ended without success. To analyze the dependency between parameters, which affected the chance of pregnancy, regression analysis was performed. RESULT(s): The mean and median for the endometrial thickness were 9.95 and 10.0 mm, (range: 7-15 mm), respectively. The endometrial thickness for cycles which resulted in pregnancy was comparable to that for cycles, which ended without success. Regression analysis revealed that age and the number of transferred embryos, which had 6 to 8 blastomeres, were the only independent variables that determined pregnancy. CONCLUSION(s): Increased endometrial thickness does not adversely affect the chance of pregnancy. Age and number of blastomeres of the transferred embryos were the independent predictors for IVF success.
Keywords: Age; Embryo; Embryo transfer; Endometrial Thickness; Pregnancy; Receptivity